Synthesis of nano Ag catalyst embeded vanadium phosphorus oxide for oxidation of styrene to benzaldehyde by hydrogen peroxide - Nguyen, Kieu Van; Nguyen, Khanh Kim; Diep, Duyen Thi; Nguyen, Hoang Van; Co, Thien Thanh (Vietnam Journal of Science and Technology, 2020)
In this work, nano silver catalyst loaded on vanadium phosphorus oxide (Ag/VPO) for oxidation of styrene to benzaldehyde was synthesized by impregnating method including impregnating of VPO substrate with colloid solution of nano silvers. VPO substrate was prepared by microwave-assisted reaction of vanadium and phosphorus precursors. Meanwhile, nano Ag/PVP was prepared in solution using NaBH4 as reducing agent and polyvinylpyrrolidone (PVP) as protecting agent and spherical-shaped nano particles with mean diameter of about 7.5 nm determined by transmission electron microscopy (TEM) was obtained.